2022
DOI: 10.3389/fimmu.2022.820366
|View full text |Cite
|
Sign up to set email alerts
|

Does the Amniotic Fluid of Mice Contain a Viable Microbiota?

Abstract: The existence of an amniotic fluid microbiota (i.e., a viable microbial community) in mammals is controversial. Its existence would require a fundamental reconsideration of fetal in utero exposure to and colonization by microorganisms and the role of intra-amniotic microorganisms in fetal immune development as well as in pregnancy outcomes. In this study, we determined whether the amniotic fluid of mice harbors a microbiota in late gestation. The profiles of the amniotic fluids of pups located proximally or di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 160 publications
1
17
0
Order By: Relevance
“…Recent experimental evidence also suggested that within‐host evolution of microbiota may occur, leading to different immune responses [27]; thus, a common GI microbiome can diverge over time, leading to distinct and repeatable shifts in bacterial species and changes in local immune strategies. It is also plausible that Pseudomonas and other gram‐negative microbes are deposited in utero ; Pseudomonas prevalence has been identified in amniotic fluid [28, 29]. Regardless of how the microbes evolve to inhabit the visceral adipose niche, gram‐negative bacterial accumulation in this extraintestinal site drives a robust immune response through nuclear factor‐κB (NF‐κB), inciting proinflammatory M1 macrophage infiltration and Th1 cytokine release [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent experimental evidence also suggested that within‐host evolution of microbiota may occur, leading to different immune responses [27]; thus, a common GI microbiome can diverge over time, leading to distinct and repeatable shifts in bacterial species and changes in local immune strategies. It is also plausible that Pseudomonas and other gram‐negative microbes are deposited in utero ; Pseudomonas prevalence has been identified in amniotic fluid [28, 29]. Regardless of how the microbes evolve to inhabit the visceral adipose niche, gram‐negative bacterial accumulation in this extraintestinal site drives a robust immune response through nuclear factor‐κB (NF‐κB), inciting proinflammatory M1 macrophage infiltration and Th1 cytokine release [30].…”
Section: Discussionmentioning
confidence: 99%
“…Recent experimental evidence also suggested that withinhost evolution of microbiota may occur, leading to different immune responses [27]; thus, a common GI microbiome can diverge over time, leading to distinct and repeatable shifts in bacterial species and changes in local immune strategies. It is also plausible that Pseudomonas and other gram-negative microbes are deposited in utero; Pseudomonas prevalence has been identified in amniotic fluid [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…The debate about whether the intrauterine environment is sterile has gained prominence with many arguing that bacterial DNA contamination from sampling sites, clinical or laboratory environments, as well as reagents and consumables, can greatly influence the results of microbiota studies, especially for low-biomass specimen types ( Salter et al, 2014 ). Consequently, several investigators have examined the effects of strict controls for contamination on subsequent sequencing demonstrating a sterile intrauterine environment ( Leiby et al, 2018 ; de Goffau et al, 2019 ; Kuperman et al, 2020 ; Olomu et al, 2020 ; Winters et al, 2022 ). Furthermore, de Goffau et al (2021) re-analyzed the data from Rackaityte et al (2020) and provided evidence that the identification of Micrococcus in fetal gut samples was contaminated and several findings were caused by an unrecognized batch effect.…”
Section: Discussionmentioning
confidence: 99%
“…The amniotic fluid samples were meticulously collected using a sterile procedure following a previously described protocol 18,19 . The abdomen of the pregnant mouse was shaved and sterile by 70% ethanol.…”
Section: Methodsmentioning
confidence: 99%
“…The amniotic fluid samples were meticulously collected using a sterile procedure following a previously described protocol. 18,19 The abdomen of the pregnant mouse was shaved and sterile by 70% ethanol. Sterile disposable scissors and forceps were utilized to remove the uterine horns and placed in a sterile dish.…”
Section: Saliva and Amniotic Fluid Sample Collectionmentioning
confidence: 99%